Stylistic Analysis of a Poem: An Inquiry into William Blake’s ‘The Lamb’ - Roy, Dr. Harimadhav (Journal of Advanced Research in Humanities and Social Sciences; Vol 4 No 1 (2017): Journal of Advanced Research in Humanities and Social Sciences, 2023)
Linguistic stylistics systematically analyses the language of a text, it objectively accounts for the meaning of a text. However, this objective scrutiny of a text is often criticised by many literary critics. They find stylistic analysis of a text is too mechanistic and cerebral in operations and instead of helping readers appreciate the text, it actually impedes the whole process of reading and appreciating literature. According to Gower (1986), “when a text is put under a microscope and readers’ attention is drawn to the analytical procedures, aesthetic qualities of the text are diminished and the readers who work under such laboratory conditions fail to appreciate the emotional appeal of the text.” Carter et al (1989) have very convincingly pointed out how a literary stylistic approach enhances the literary experience of the readers. Linguistic stylistics provides the readers with necessary tools and techniques to understand the aesthetic qualities of the text and also sensitise them to the intricacies of literature which may help them in interpreting the text in a better way. The aim of this paper is to explore different perspective to analyze a poem and what are the techniques and tools that the reader should keep in mind while reading or interpreting a poem? The author looks into perspectives of Stylistics and analyzes William Blake’s ‘The Lamb’which appeared in ‘Songs of Innocence’ (1789). How to cite this article: Ray HM, Stylistic Analysis of a Poem: An Inquiry into William Blake’s The Lamb. J. Adv. Res. Humani. Social Sci. 2017; 4(1): 1-7.